Formation and distribution of international tourism flows in geographical space - Oleksandr Korol (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
Properties of geographical space that are of key importance for international tourism, as length and discreteness, are analyzed in the article. Length makes tourists cover distances, whereas discreteness manifests itself in spatial heterogeneity. Tourism in conditions of homogeneous space is vain. That is, heterogeneity brings sense to travels as well as determines their direction. So, the effect of geographical space’s length and spatial heterogeneity on formation and distribution of tourism flows is assessed, international tourism’s geographical essence is disclosed also.